2022
DOI: 10.1016/j.red.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of health over the life cycle

Abstract: We construct a unified objective measure of health status: the frailty index, defined as the cumulative sum of all adverse health indicators observed for an individual. First, we show that the frailty index has several advantages over self-reported health status, particularly when studying health dynamics. Then we estimate a stochastic process for frailty dynamics over the life cycle. We find that the autocovariance structure of frailty in panel data strongly supports a process that allows the conditional vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 76 publications
(65 reference statements)
2
8
0
Order By: Relevance
“…Seehttps://www.disabilityrightsuk.org/wca-limited-capabilitywork-assessment-descriptors for details.17 This distribution is consistent with the finding ofHosseini et al (2021) on the life-cycle dynamic of a frailty index built using PSID data.…”
supporting
confidence: 69%
“…Seehttps://www.disabilityrightsuk.org/wca-limited-capabilitywork-assessment-descriptors for details.17 This distribution is consistent with the finding ofHosseini et al (2021) on the life-cycle dynamic of a frailty index built using PSID data.…”
supporting
confidence: 69%
“…Secondly, it enables a greater modelling of inequalities and the considerable diversity in how people age (Hosseini, Kopecky and Zhao (2022)).…”
Section: The Importance Of Biological Agementioning
confidence: 99%
“… Dalgaard and Strulik (2014) were among the earliest to view the frailty index with these characteristics as a comprehensive measure of human health status and to introduce it into economic analysis. More recently, Hosseini et al (2022) proposed their own frailty index, compared it with self-reported health status, and reported interesting results showing significant differences in the ability to predict health outcomes. An important point about the health damage variable is that it reflects so-called senescence, even though it is partly related to normal aging.…”
Section: Related Literaturementioning
confidence: 99%